Construction and application of a stratified nursing intervention program for postoperative delirium after Stanford type A aortic dissection: a quasi-experimental trial - Xueping Li; Miaomiao Zheng; Ailin Lin; Chaohong Chen; Yuanbo Wu; Huai Zhang; Zhiqin Yin (Perioperative Medicine)
Abstract Background Postoperative delirium is a common and significant consequence in patients with type A aortic dissection following surgery; however, there is currently no effective postoperative care plan. Objective The purpose of this study is to develop and evaluate the practical implementation of a stratified nursing intervention program for postoperative delirium in patients undergoing surgery for Stanford type A aortic dissection. Methods A stratified nursing intervention program for postoperative delirium was created using a literature review, group discussions, and the Delphi method via expert mail inquiry. A quasi-experimental design was used, with patients admitted to the general ward of a tertiary hospital in Wenzhou, China, functioning as subjects. From September to December 2022, 43 patients were included in the control group and given standard treatment. From January to June 2023, 37 patients were recruited in the intervention group, receiving both routine care and the intervention plan. The intervention’s effects were compared in the two groups. Results The intervention group had considerably shorter delirium and hospital stays than the control group (P < 0.05), as well as higher patient satisfaction levels. There were no inadvertent extubations in the intervention group. When the incidence and beginning time of delirium in the general ward were compared, there were no significant differences between the two groups (P > 0.05). Conclusion Implementing this nurse intervention in the ward context can shorten postoperative delirium and hospital stays, increase patient satisfaction with care, and improve patient prognosis and quality of life. This intervention will also serve as a great resource for future clinical management of postoperative delirium. Trial registration The National Health Security Information Platform’s Medical Research Registration Information System has registered this study under the registration number MR-33–22-022978.